Local wisdom of Talang Mamak Tribe, Riau, Indonesia in supporting sustainable bioresource utilization - PRIMA WAHYU TITISARI; ELFIS ELFIS; IRINA SAFITRI ZEN; KHAIRANI KHAIRANI; NADIATUL JANNA; NUNUT SUHARNI; TIKA PERMATA SARI (Society for Indonesian Biodiversity, 2019)
Titisari PW, Elfis, Zen IS, Khairani, Janna N, Suharni N, Sari TP. 2019. Local wisdom of Talang Mamak Tribe, Riau, Indonesia in supporting sustainable bioresource utilization. Biodiversitas 20: 190-197. Study the Talang Mamak tribe is an isolated community that lives traditionally in the downstream Indragiri River, Riau Province, Indonesia. This tribe is one of the oldest Malay tribes (Proto Malay), relatively still maintaining hunting and gathering mode of life even though now some of them began to settle and farm. The study aims to identify their local wisdom and analyze it in the context of bioresource utilization to sustain their living needs. Data were collected through observation, interviews, documentation, and triangulation. The informants to be interviewed were selected using purposive sampling. The study showed that the local wisdom of Talang Mamak Tribe had sustainable dimension in managing bioresources which inherited from their ancestors. This cultural heritage guides the community to always live in harmony with the universe which is reflected in ritual activities such as melambas and basolang menugal (clearing land for farming), manumbai (harvesting timber from the forest) and manjumbai (harvesting honey). Sociologically, the traditions or customs carried out by the Talang Mamak tribe are an effort to preserve and maintain bioresource, so as to create a balance of relations between humans and nature.